2008
DOI: 10.2139/ssrn.1288743
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Supply Reliability in a Retail Setting with Joint Marketing and Inventory Decisions

Abstract: T his paper studies the impact of supply reliability on a retail firm's performance under joint marketing and inventory decisions. The firm sells a product in a single selling season and can exert marketing effort to influence consumer demand. We develop a modeling framework to quantify the value of improving supply reliability and investigate how this value depends on different model parameters. Our results provide useful insights into how firms should make investment decisions on adopting new technologies to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 19 publications
2
39
0
Order By: Relevance
“…Lee and Yano (1988) study a multi-stage model for a single production run to meet a single-period demand. Liu et al (2008) consider the impact of supply reliability on inventory and pricing decisions. On a related topic, Bollapragada et al (2004) consider assembly systems with random capacity at each location that are controlled with base-stock policies.…”
Section: Causes Of Inventory Inaccuracy and Related Literaturementioning
confidence: 99%
“…Lee and Yano (1988) study a multi-stage model for a single production run to meet a single-period demand. Liu et al (2008) consider the impact of supply reliability on inventory and pricing decisions. On a related topic, Bollapragada et al (2004) consider assembly systems with random capacity at each location that are controlled with base-stock policies.…”
Section: Causes Of Inventory Inaccuracy and Related Literaturementioning
confidence: 99%
“…They also compared the certain and uncertain yield cases and illustrated that certain yield situation brings better system performance. Liu et al (2010) present another related study in which demand is manipulated and determined as a result of marketing effort, whereas product price is fixed. Not surprisingly, when marketing effort is high, demand increases and it further increases the profit.…”
Section: Random Yieldmentioning
confidence: 99%
“…Liu et al [41] considered how supply reliability influences the performance of a retail firm under joint marketing and inventory decisions. They investigated the value of higher supply reliability and showed that the optimal stocking quantity does not necessarily increase or decrease as risk is reduced due to the improvement of supply reliability.…”
Section: Inventory Protectionmentioning
confidence: 99%
“…Carrying enough inventory to protect against a disruption that could last weeks or even months is completely antithetical to the lean strategies pursued by firms in many industries. Moreover, studies have shown that if the premium cost of using a reliable supplier is comparable with the cost of holding inventory against supply disruptions, it is preferable to make use of reliable suppliers [41]. The reason is that lowered inventory levels reveal problems more quickly and hence are conducive to problem resolution and process improvement.…”
Section: Redundancy Planningmentioning
confidence: 99%